Examining the Adoptability of Cryptocurrency in the Islamic Financial System: Perspectives from Sharīʿah Scholars - Naz, Samina (Journal of King Abdulaziz University: Islamic Economics, 2024)
This study explores the adoptability of cryptocurrency within the Islamic financial system, a topic of substantial debate among scholars and practitioners. Given the decentralized nature of cryptocurrency, its acceptance within the conventional and Islamic financial systems presents unique challenges. To ascertain the legitimacy and possible adoptability of cryptocurrency under Sharīʿah law, this paper employs qualitative research methods, using in-depth interviews of twenty-four Sharīʿah scholars. These scholars, selected through purposive and snowball sampling techniques, possess expert knowledge of both cryptocurrency and the Islamic financial system. The results revealed that the acceptability of cryptocurrency in Sharīʿah-compliant financial systems is contingent on its centralization and its function as a store of value, aligning with the objectives (maqasid) of Sharīʿah. Cryptocurrency's lack of intrinsic value necessitates its backing by a central authority or asset to mitigate risks and potential fraud. This research offers valuable insights into the considerations required for cryptocurrencies' adoption in Islamic finance, contributing to the ongoing debate on their legitimacy under Sharīʿah law.